2020
DOI: 10.21203/rs.3.rs-21697/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The action of the Cu2+, Ag+ and time inducing the in vitro anther culture-derived barley regenerants

Abstract: BackgroundPlant regeneration via anther cultures is a world-wide approach as it allows for the regeneration of uniform and homozygous double haploids. Recent studies have shown that in vitro cultures are the origin of the so-called tissue culture-induced variation (TCIV) that may lead to off-type regenerants. Moreover, the regeneration of green plants may be limited by the presence of albinos. It was demonstrated that the presence of Cu2+ and Ag+ ions in the regeneration medium might increase the number of gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Silver nitrate (AgNO 3 ) could promote ethylene production in vitro organogenesis by inhibiting ethylene action sites and was proved to be effective for bud induction and regeneration at proper concentration Zhuang 2002, Bednarek andOrłowska 2020). By adding various concentrations of AgNO 3 , it was found that the lower concentrations of AgNO 3 (0.5 mg/l and 1.0 mg/l) could obviously promote the elongation of the both pair of lateral buds than the higher concentrations after 50 days cultivation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Silver nitrate (AgNO 3 ) could promote ethylene production in vitro organogenesis by inhibiting ethylene action sites and was proved to be effective for bud induction and regeneration at proper concentration Zhuang 2002, Bednarek andOrłowska 2020). By adding various concentrations of AgNO 3 , it was found that the lower concentrations of AgNO 3 (0.5 mg/l and 1.0 mg/l) could obviously promote the elongation of the both pair of lateral buds than the higher concentrations after 50 days cultivation (Fig.…”
Section: Resultsmentioning
confidence: 99%